2010
DOI: 10.1371/journal.pone.0012852
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of 8-Hydroxyquinoline with Soil Environment Mediates Its Ecological Function

Abstract: BackgroundAllelopathic functions of plant-released chemicals are often studied through growth bioassays assuming that these chemicals will directly impact plant growth. This overlooks the role of soil factors in mediating allelopathic activities of chemicals, particularly non-volatiles. Here we examined the allelopathic potential of 8-hydroxyquinoline (HQ), a chemical reported to be exuded from the roots of Centaurea diffusa.Methodology/Principal FindingsGrowth bioassays and HQ recovery experiments were perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Microbial degradation is the reason most often given to explain microbial reductions of allelopathic effects, and it has been demonstrated in studies that have found increased growth of bioassay plants along with reduced recovery of allelochemicals under non-sterile conditions (Inderjit and Foy, 1999;Chiapusio and Pellissier, 2001;Inderjit et al, 2010). As expected, recovery of many allelochemicals such as phenolic acids, saponins, isothiocyanates, and flavonoid glycosides spiked into soils is greater in sterile than nonsterile soils (Blum et al, 1994;Okumura et al, 1999;Weidenhamer and Romeo, 2004;Furubayashi et al, 2005;Barto and Cipollini, 2009b;Chen et al, 2011).…”
Section: Microbial Protection From Allelopathymentioning
confidence: 85%
See 1 more Smart Citation
“…Microbial degradation is the reason most often given to explain microbial reductions of allelopathic effects, and it has been demonstrated in studies that have found increased growth of bioassay plants along with reduced recovery of allelochemicals under non-sterile conditions (Inderjit and Foy, 1999;Chiapusio and Pellissier, 2001;Inderjit et al, 2010). As expected, recovery of many allelochemicals such as phenolic acids, saponins, isothiocyanates, and flavonoid glycosides spiked into soils is greater in sterile than nonsterile soils (Blum et al, 1994;Okumura et al, 1999;Weidenhamer and Romeo, 2004;Furubayashi et al, 2005;Barto and Cipollini, 2009b;Chen et al, 2011).…”
Section: Microbial Protection From Allelopathymentioning
confidence: 85%
“…While the importance of abiotic soil factors with respect to the alteration and influence of allelochemicals cannot be stressed enough (Inderjit et al, 2010), microbial transformations and the general role of microbes with respect to allelochemicals clearly plays a major role in influencing allelopathic effects (Inderjit, 2005). In addition to detoxifying allelochemicals through degradation, however, soil microbial communities also have been shown to degrade toxic compounds into more toxic products (e.g., Gagliardo and Chilton, 1992) and to degrade relatively innocuous substances into toxic products.…”
Section: Microbial Enhancement Of Allelopathymentioning
confidence: 99%
“…For blank titration, similarly prepared boxes but without soil were used. The CO 2 release from non-Mikania soil and Mikania soil was calculated following Inderjit and Rajeswari (2010). Mean and 95% CI of the two groups at each site were compared for differences.…”
Section: Soil Respirationmentioning
confidence: 99%
“…Furthermore, while moving through the soil, allelochemicals might undergo transformation, as various factors within the soil environment, such as the physical, chemical, biological and physicochemical properties of the soil, can influence the activities of allelochemicals. Due to these interactions, the role of the soil should not be ignored in studies of the allelopathic potential of a plant (Inderjit et al, 2010). Indeed, the isolation and identification of chemicals from donor plants with biological activity does not necessarily demonstrate that these compounds interfere in nature through allelopathy (Inderjit, 2000).…”
Section: Introductionmentioning
confidence: 99%